THE EFFECT OF INTRUSION ON THE PHYSICAL AND CHEMICAL PROPERTIES OF COAL - Ogara, Evan Rosyadi; Tri Wahyuni; Al Hussein Flowers Rizqi (JGE (Jurnal Geofisika Eksplorasi), 2025)
Coal is a deposit of organic matter derived from plant remains that have undergone diagenesis process to form a coal seams. This study aims to determine the impact of intrusion on the physical and chemical characteristics of coal. The location of this research is in the Air Laya mining area, PT Bukit Asam Tbk, Tanjung Enim, South Sumatra and is part of the South Sumatra Basin which is well known as one of the coal bearing formation areas. Four (4) coal samples were analysed including proximate analysis, total sulphur content, and calorific value to measure moisture content, volatile matter, fixed carbon, ash content, and calorific value of the coal. Petrology and well log analysis was used to determine lithology and regression analysis was used to assess the effect of intrusion on coal characteristics. The results of the coal analysis in the research area reveal significant differences between coal samples located near the intrusion and those farther away. Coal located near the intrusion exhibits black colour, vitreous and conchoidal fracture. In contrast, coal farther from the intrusion shows a dull, blackish-brown, brownish streak, and uneven fracture. Coal near the intrusion shows lower moisture (1.5–1.7%) and volatile matter (17–25%), but higher ash content (7.9–8.2%), fixed carbon (67–73%), calorific value (7700–7968 kcal/kg), and sulphur (0.7–0.8%). In the other hand, coal farther from the intrusion has higher moisture and volatile matter, but lower fixed carbon, calorific value, and sulphur. The findings conclude that proximity to intrusion increases fixed carbon and calorific value but also raises sulphur levels, which may pose environmental and operational concerns.